Minimally Invasive Surgery of the Lumbar Spine - Menchetti, Pier Paolo Maria; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
Minimally or noninvasive surgical techniques have profoundly changed the way surgeons operate today. The possibility of offering the patient a selection of spinal surgical procedures, based on mediating the consequences of surgery while maximizing the results of the procedure has resulted in a growing interest in minimally invasive spinal surgery (MISS). MISS is a multidisciplinary subject involving the orthopedic surgeon, neurosurgeon, radiologists, anesthesiologists and pain management specialists, each of which needs to act in unison to maximize the benefit to the patient.   Minimally Invasive Surgery of the Lumbar Spine represents the first multidisciplinary review of the topic in which the focus is on the management of the patient throughout the perioperative period. The Editor and his carefully selected group of Contributors focus on correct diagnoses using the most appropriate imaging. The book reviews anesthesiology techniques, the optimal minimally invasive approach, treatment of lumbar disc herniation and degenerative disc disease, and the most advanced applications of robotic surgery. It will therefore be vital reading for all spinal orthopedic surgeons, neurosurgeons, pain management specialists, anesthesiologists, and interventional radiologists involved in the management of patients who would benefit from MISS procedures.
Anesthesia and Perioperative Care in MISS -- Diagnostic imaging of degenerative spine diseases -- Radiofrequency Lumbar Facet Joint Denervation -- Percutaneous treatment in lumbar disc herniation -- Assessment and Selection of the Appropriate Individualized Technique for Endoscopic Lumbar Disc Surgery -- Interspinous devices: State of the Art -- Less-invasive decompression and posterolateral fusion using ILIF with or without supplemental TLIF -- Minimal invasive Posterior Dynamic Stabilization: A new treatment option for disc degeneration -- Percutaneous pedicle screws in the lumbar spine -- Minimally invasive lumbar spine surgery: current status -- Lumbar Nucleus Replacement -- Vertebral body augmentation in osteoporotic vertebral compression fractures -- The Sacroiliac Joint: A Minimally Invasive Approach -- Image- and Robotic Guidance in Spine Surgery -- Bone substitution in spine fusion: the past, the present, the future -- Microsurgical approach for the treatment of juxtafacet synovial cysts of the lumbar spine.
Keywords: Orthopedics; Minimally invasive surgery; Orthopedics; Minimally Invasive Surgery